Prevalence and Clinical Correlates of Self-Harm Behaviors in Gilles de la Tourette Syndrome - Szejko, Natalia; Jakubczyk, Andrzej; Janik, Piotr (Frontiers in Psychiatry, 2019)
Introduction: Major symptoms of Gilles de la Tourette syndrome (GTS) are tics, but in 90% of cases, psychiatric comorbidities occur. Self-harm behaviors (SHBs) could result from deliberate action and unintentional injury from tics. Methods: We examined 165 consecutive GTS patients aged 5 to 50 years (75.8% males). The median duration of GTS was 14 years (interquartile range, 9–22 years). The patients were evaluated for GTS and comorbid mental disorders according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision. Self-harm behavior was diagnosed during the interview. To determine a direct relationship between SHB and clinical variables, we conducted two analyses, at the time of evaluation and lifetime. We also compared the group of children and adults with SHB. We also tried to distinguish between deliberate (non–tic-related SHB) and accidental (tic-related SHB). Results: Lifetime SHB was reported by 65 patients (39.4%), and in 55 of the cases, it was present at the time of evaluation. The age at the onset of SHB was reported in 55 of the cases (84.6%), and the median was 10 years (interquartile range, 7–13 years). In 30 of the patients (46.2%), SHB was evaluated as mild; in 26 (40%), as moderate; and in only 9 cases (13.9%), as severe. In the multivariable analysis for the predictor of lifetime SHB, attention-deficit/hyperactivity disorder (p = 0.016) and obsessive-compulsive disorder (OCD; p = 0.042) were determined as risk factors, while for current SHB, only tic severity (p < 0.0001) was statistically significant. When comparing predictors of SHB for children and adults, tic severity was determined as predictor for lifetime SHB in children (p < 0.0001), while the anxiety disorder was associated with lifetime SHB in adults (p = 0.05). Similarly, tic severity was a predictor of current SHB in the children group (p = 0.001), but this was not confirmed for adults. The group of patients with tic-related and non–tic-related SHB did not differ. Conclusions: Self-harm behavior appears mostly in children and adolescents and rarely begins in adulthood. Self-harm behavior is associated mainly with tic severity, obsessive-compulsive disorder, and attention-deficit/hyperactivity disorder. Clinical correlates of SHB are age related and differ at different points of life. Tic severity is the main factor associated with SHB in children. In the adult group, anxiety disorder and other psychiatric comorbidities may play the most important role.